The Trafficking of Filipino Women in Japan: Intervention Efforts - Nuqui, Carmelita G. (Philippine Journal of Labor and Industrial Relations; Vol 26 (2006): Philippine Journal of Labor and Industrial Relations, 2021)
Non-government organizations play a vital role in the fight against human trafficking. Their work with victims of trafficking and with other concerned networks and organizations has resulted in greater public awareness of the issue. NGOs are also active in consciousness-building, information dissemination, education and training, providing data and information, providing direct services to victims, as well as lobbying for the passage of laws. Likewise, NGOs are critical allies and partners of government in the fight against this modern day form of slavery.  This paper provides a descriptive discussion and analysis of trafficking of Filipino women outside the Philippine borders while focusing on the Development Action for Women Network (DAWN) and how its programs and services have made a difference in the lives of its members.